Why do Entrepreneurial Parents have Entrepreneurial Children? - Matthew Lindquist; Joeri Sol; Mirjam van Praag (Tinbergen Institute, 2012)
Parental entrepreneurship is a strong, probably the strongest, determinant of own entrepreneurship. We explore the origins of this intergenerational association in entrepreneurship. In particular, we identify the separate effects of pre- and post-birth factors (nature and nurture), by using a unique dataset of Swedish adoptees. Its unique characteristic is that it not only includes data on occupational status for the adoptees and their adoptive parents, but also for their biological parents. Moreover, we use comparable data on entrepreneurship for a large, representative sample of the Swedish population. Based on the latter sample, and consistent with previous findings, we show that parental entrepreneurship increases the probability of children's entrepreneurship by about 60%. We further show that for adoptees, both biological and adoptive parents make significant contributions. These effects, however, are quite different in size. The effect of post-bir th factors (adoptive parents) is approximately twice as large as the effect of pre-birth factors (biological parents). The sum of these two effects for adopted children is almost identical to the intergenerational transmission of entrepreneurship for own-birth children. We explore several candidate explanations for this important post-birth effect and present suggestive evidence in favor of role modeling.
Keywords: J24; J62; L26; 330; adoption; entrepreneurship; self-employment; intergenerational mobility; occupational choice; role model; Unternehmer; Selbstständige; Generationengerechtigkeit; Berufswahl; Schweden